THE INFLUENCE OF PERCEIVED USEFULNESS, PERCEIVED EASE OF USE, PERCEIVED ENJOYMENT, AND TRUST ON INTENTION TO REUSE - Ni Luh Putu Ayu Diah Sawitri M; I Gde Ketut Warmika (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
This research is motivated by Shopee being one of the most popular shopping sites and much in demand for purchasing products online, but there are still doubts among consumers to reuse the Shopee marketplace as a place to shop or transact online for the first time or repeatedly. Shopee must try to improve its services so that consumers' intention to reuse Shopee is higher. This study aims to explain the influence of perceived usefulness, perceived ease of use, perceived enjoyment, and trust on the intention to reuse the Shopee marketplace among Shopee consumers in Denpasar City. The research sample consists of 120 Shopee consumers aged at least 17 years, with a minimum education level of high school or equivalent, residing in Denpasar City, and having made at least 3 purchases on the Shopee site in the past 3 months. Data collection method used a questionnaire instrument. Data analysis techniques employed were descriptive statistical analysis and multiple linear regression. The research findings indicate that, partially, perceived usefulness, perceived ease of use, perceived enjoyment, and trust have a positive and significant influence on reuse intention. The implications of this research highlight the need for attention to strategies related to usefulness, ease of use, convenience, and trust on Shopee if they intend to maintain consumer intention to reuse Shopee marketplace as their online shopping platform.